NODULAÇÃO DO FEIJOEIRO E FIXAÇÃO BIOLÓGICA DO NITROGÊNIO EM RESPOSTA À MICROBIOLIZAÇÃO DAS SEMENTES E À APLICAÇÃO DE MICRONUTRIENTES - Kusdra, Jorge Ferreira (Scientia Agraria, 2003)
During 2001, four experiments were carried out at Crop Science Departments greenhouse of the Federal University of Paraná, in Curitiba, PR, using bean (Phaseolus vulgaris L.), varieties FT Bionobre and FT Bonito. The objective was to evaluate the isolated and combined effects of Rhizobium tropici, Bacillus subtilis, molybdenum, and cobalt, added through the seed, on the root nodulation and biological nitrogen fixation, plant growth and on the grain production. The experiments, two for each variety, were installed in the same way, using a complete randomized design in a 24 factorial arrangement, considering as factors the Rhizobium tropíci, Bacillus subtilis, molybdenum and cobalt, all in two levels, absence and presence, with 16 treatments, four replications and 64 experimental units. Two experiments were evaluated in the R6 development stage, considering indicative variables of the plant growth and of the nodulation and biological nitrogen fixation. The other two experiments were evaluated in the end of the R9 development stage, considering indicative variables of the production and grain yield. The experimental results showed that the Rhizobium tropici was not able to increase nodular weight and size as well as total nitrogen content in the aerial part, regardless variety. The Bacillus subtilis didnt influence in the nodulation and grain production for both varieties contributing, however, for the increase of the plant growth of the FT Bionobre variety. The molybdenum enhanced the total nitrogen content in the aerial part, pods and grains number, as well as grain weight for FT Bionobre variety, suggesting a potential for increasing crop yield. The cobalt had greater influence in FT Bonito variety where it reduced the total nodules number and increased 100-grain weight. It was not verified, in both varieties, any combination among Rhizobium tropíci, Bacillus subtilis, molybdenum, and cobalt added through the seeds that resulted in improved nodulation or increase in grain production.